Hydrophobically modified poly(vinyl alcohol) using alkoxy-substituted methyl gallate: synthesis and rheology - Shedge, Aarti S.; Wadgaonkar, Prakash P.; Lele, Ashish K.; Badiger, Manohar V. (Journal of Polymer Science Part B-Polymer Physics, 2010)
Hydrophobically modified poly(vinyl alcohol) (HMPVA) polymers were synthesized by potassium t-butoxide-catalyzed reaction of PVA with methyl 3,4,5-tris(n-octyloxy) benzoate (MGC(8))/3,4,5-tris(n-dodecyloxy) benzoate (MGC(12)) and 1,3-propane sultone. The concentration of 1,3-propane sultone was kept constant at 10 mol %. and that of MGC(8) (2, 3, and 4 mol %)/MGC(12) (2 and 3 mol %) was varied to obtain HMPVAs with different hydrophobic contents. The incorporation of MGC(8)/MGC(12) and 1,3-propane sultone onto HMPVA was confirmed by NMR spectroscopy. Rheological properties of aqueous solutions also confirmed the presence of hydrophobic and charged functional groups on HMPVAs. In the semidilute regime, the specific viscosity of HMPVAs followed concentration scaling that is typical of polyelectrolytes. At higher concentrations, the HMPVA solutions with 3 and 4 mol % of MGC(8) exhibited large increase in specific viscosity. Oscillatory experiments on these solutions exhibited gel-like behavior at polymer concentrations of 40-50 g/L. Confocal microscopy images of HMPVA with 4 mol % of MGC(8) clearly indicated the existence of microgels. The tendency of formation of microgels further increased with increasing chain length of the hydrophobe, that is, with MGC(12). These samples exhibited rheological behavior that is typical of soft solids and was therefore probed by the strain-rate frequency superposition technique reported recently in the literature. HMPVAs with improved rheological properties show potential applications as thickeners in cosmetic creams, lotions and as drug carriers in pharmaceutical formulations. (C) 2010 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 48: 1054-1063, 2010
Keywords: gallic acid; hydrophobically modified poly(vinyl alcohol); Rheology; water-soluble polymers

Hydrophobically Modified Chitosan - Shedge, Aarti S.; Badiger, Manohar V. (Hydrophobically Modified Chitosan, 2014)
Hydrophobically modified chitosan was prepared using the hydrophobic compound derived from natural resource material such as cashew nut shell liquid. Chitosan was modified using 3-pentadecyl cyclohexane carbaldehyde to different extents (2, 3, and 5 mol%). Solution properties of hydrophobically modified chitosan were studied by rheology and light scattering. These indicated the aggregation behavior above the critical association concentration. Further, it was concluded that above the critical association concentration, the dynamics of the network formed due to the associations slowed down significantly.

Thermo-reversible sol-gel transition of aqueous solutions of patchy polymers - Parmar, Indravadan A.; Shedge, Aarti S.; Badiger, Manohar V.; Wadgaonkar, Prakash P.; Lele, Ashish K. (RSC Advances, 2017)
While aqueous solutions of several amphiphilic thermo-reversible polymers show gelation upon heating, there are fewer examples of polymer solutions that exhibit gelation when cooled. This paper reports an interesting phenomenon of abrupt thermoreversible gelation of aqueous solutions of a hydrophobically modified polymer upon cooling. A high molecular weight precursor copolymer (PCP, (M-w) over bar approximate to 5 x 10(6) g mol(-1)) of N, N-dimethylacrylamide (70 mol%) and acrylic acid (30 mol%) was modified by reacting 10 mol% of the acrylic acid groups with n-dodecyl amine to form a hydrophobically modified copolymer (HMCP). The composition of the copolymer was ascertained using NMR spectroscopy. Cooling the solution of PCP at a controlled rate resulted in a gradual increase in its low shear viscosity as dictated by the flow activation energy. In contrast, cooling the solution of HMCP under identical conditions resulted in an abrupt and large non-Arrhenius increase in viscosity at a specific transition temperature, which decreased with decrease in polymer concentration. Fluorescence measurements and dynamic light scattering data showed that abrupt gelation happened upon cooling, when polymer coils percolate accompanied with concomitant transition in chain conformation from compact micellar coils formed by intra-chain hydrophobic associations to swollen polymer coils connected by inter-chain hydrophobic interactions.